IBT-V02: A Multicomponent Toxoid Vaccine Protects Against Primary and Secondary Skin Infections Caused by Staphylococcus aureus - Karauzum, Hatice; Venkatasubramaniam, Arundhathi; Adhikari, Rajan P.; Kort, Tom; Holtsberg, Frederick W.; Mukherjee, Ipsita; Mednikov, Mark; Ortines, Roger; Nguyen, Nhu T. Q.; Doan, Thien M. N.; Diep, Binh An; Lee, Jean C.; et al. (Frontiers in Immunology, 2021)
Staphylococcus aureus causes a wide range of diseases from skin infections to life threatening invasive diseases such as bacteremia, endocarditis, pneumonia, surgical site infections, and osteomyelitis. Skin infections such as furuncles, carbuncles, folliculitis, erysipelas, and cellulitis constitute a large majority of infections caused by S. aureus. These infections cause significant morbidity, healthcare costs, and represent a breeding ground for antimicrobial resistance. Furthermore, skin infection with S. aureus is a major risk factor for invasive disease. Here we describe the pre-clinical efficacy of a multicomponent toxoid vaccine (IBT-V02) for prevention of S. aureus acute skin infections and recurrence. IBT-V02 targets six S. aureus toxins including the pore-forming toxins alpha hemolysin (Hla), Panton-Valentine leukocidin (PVL), leukocidin AB (LukAB), and the superantigens toxic shock syndrome toxin-1 and staphylococcal enterotoxins A and B. Immunization of mice and rabbits with IBT-V02 generated antibodies with strong neutralizing activity against toxins included in the vaccine, as well as cross-neutralizing activity against multiple related toxins, and protected against skin infections by several clinically relevant S. aureus strains of USA100, USA300, and USA1000 clones. Efficacy of the vaccine was also shown in non-naïve mice pre-exposed to S. aureus. Furthermore, vaccination with IBT-V02 not only protected mice from a primary infection but also demonstrated lasting efficacy against a secondary infection, while prior challenge with the bacteria alone was unable to protect against recurrence. Serum transfer studies in a primary infection model showed that antibodies are primarily responsible for the protective response.